Baseline serum triglyceride predicts early-onset peritonitis and prognosis in incident CAPD patients. Issue 2 (15th January 2021) - Wan, Sheng; Tian, Hongdan; Cheng, Li; Ding, Yanqiong; Luo, Qing; Zhang, Yanmin
Abstract : Abstract: We aimed to investigate the hypothesis that serum triglyceride (TG) may be an independent predictor of early-onset peritonitis and prognosis in incident continuous ambulatory peritoneal dialysis (CAPD) patients. In this retrospective, observational study, we screened 291 adults admitted to the PD center of the Wuhan No. 1 hospital from August 1, 2013 to November 31, 2017. All biochemical data were collected at the first 1 to 3 months after the initiation of CAPD. Early-onset peritonitis was defined as peritonitis occurring within 6 months after the initiation of PD. All of PD patients were followed up to July 31, 2018. The primary endpoint was the incidence of early-onset peritonitis while the second endpoints included overall mortality and technical failure. A total of 38 patients occurred early-onset PD peritonitis and the Lasso logistic regression selected TG and age in the final model for early-onset peritonitis. We divided patients into two groups based on the median baseline TG levels: TG ≥ 1.4mmo/L group (n = 143) and TG < 1.4mmol/L group (n = 148). There were 34 (11.7%) patients died and 33 (11.3%) patients transferred to hemodialysis during the follow-up, Moreover, a level of TG ≥ 1.4mmol/L at the initiation of CAPD was associated with a significantly increased probability of technical failure (hazard ratio, HR, 1.30; 95% confidence interval, 95% CI, 1.09 to 2.19, P  = .043) and overall mortality (HR, 2.33; 95% CI, 1.16–4.72, P  = .018). Serum TG levels measured at the initiation of PD therapy is an independent predictor of early-onset peritonitis and prognosis of CAPD patients.